PENGARUH PROMOSI DAN KEPERCAYAAN TERHADAP KEPUTUSAN ORANG TUA MENDAFTARKAN ANAK DI MADRASAH IBTIDAIAH SALAFIYAH WARENG PURWOREJO - Muzayyanah, Iim; Abidin, Munirul; Qomarudin , A. (re-JIEM (Research Journal of Islamic Education Management), 2023)
Educational institutions, as service providers in their management, need to develop effective promotional strategies, especially in an era filled with intense competition. This is because parents today are increasingly cautious when choosing educational institutions for their children, especially at the primary education level. In addition to promotional efforts, it is also important to pay attention to and build public trust in these educational institutions. This study was conducted to determine the effect of promotion and parental trust on the decision of parents to enroll their children in Madrasah Ibtidaiah Salafiyah Wareng Butuh Purworejo and to analyze school promotion, parental trust, and their influence on the decision of parents to enroll their children in Madrasah Ibtidaiah Salafiyah Wareng Butuh Purworejo. The study used a quantitative-descriptive approach. The data used is primary data collected using a questionnaire, then analyzed using SmartPLS 3. The results of this study show that promotion and trust have a positive and significant effect on parents' decisions to enroll their children in Madrasah Ibtidaiah Salafiyah Wareng, both partially and simultaneously. This is indicated by the t-statistics value, which is greater than 1.96, and the p-values, which are smaller than 0.05. The r-square value of 0.573 also shows that the promotion and trust variables have an influence on the decision of parents to register their children at Madrasah Ibtidaiah Salafiyah Wareng by 57.3%.